Antimicrobial and Antioxidant Performance of Various Essential Oils and Natural Extracts and Their Incorporation into Biowaste Derived Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) Layers Made from Electrospun Ultrathin Fibers - Figueroa-Lopez, Kelly J. (Nanomaterials (Basel), 2019)
In this research, the antibacterial and antioxidant properties of oregano essential oil (OEO), rosemary extract (RE), and green tea extract (GTE) were evaluated. These active substances were encapsulated into ultrathin fibers of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) derived from fruit waste using solution electrospinning, and the resultant electrospun mats were annealed to produce continuous films. The incorporation of the active substances resulted in PHBV films with a relatively high contact transparency, but it also induced a slightly yellow appearance and increased the films opacity. Whereas OEO significantly reduced the onset of thermal degradation of PHBV, both the RE and GTE-containing PHBV films showed a thermal stability profile that was similar to the neat PHBV film. In any case, all the active PHBV films were stable up to approximately 200 °C. The incorporation of the active substances also resulted in a significant decrease in hydrophobicity. The antimicrobial and antioxidant activity of the films were finally evaluated in both open and closed systems for up to 15 days in order to anticipate the real packaging conditions. The results showed that the electrospun OEO-containing PHBV films presented the highest antimicrobial activity against two strains of food-borne bacteria, as well as the most significant antioxidant performance, ascribed to the films high content in carvacrol and thymol. Therefore, the PHBV films developed in this study presented high antimicrobial and antioxidant properties, and they can be applied as active layers to prolong the shelf life of the foods in biopackaging applications.